ОПТИМІЗАЦІЯ ЯКОСТІ ЕЛЕКТРОЕНЕРГІЇ ПРИ НЕВИЗНАЧЕНОСТІ ІНФОРМАЦІЇ - Кузнецов, В.Г.; Тугай, Ю.І. (Інститут електродинаміки Національної академії наук України, 2023)
The concept of forming an objective function for solving the problem of the quality of electrical energy optimizing  in power networks is proposed, which takes into account the uncertainty factor of information about the mode parameters. This will allow, in contrast to the traditional binary function of assessing the quality of electrical energy for compliance with the established standards, to take into account the dynamics of changes in the efficiency criterion and perform the search for optimal values of the relevant controlling influences. The classification of information flows about the mode of the electric network is presented and the boundaries of fuzzy set for the values of the mode parameters are defined. It is shown that the objective function should be appropriately formed on the basis of fuzzy logic. The principles of the formation of fuzzy mathematical models for the analysis of established normal modes of the electrical network are defined. It is proposed to determine the membership function of a fuzzy set taking into account the quality of information that can be provided by the technical means of the electrical network. Ref. 5, table, fig. 3.